Answer:
<h3>The option A)
![x^{10}z^7](https://tex.z-dn.net/?f=x%5E%7B10%7Dz%5E7)
is correct answer.</h3><h3>The correct simplification for the given expression
![\frac{x^{12}\times z^{11}}{x^2\times z^4}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E%7B12%7D%5Ctimes%20z%5E%7B11%7D%7D%7Bx%5E2%5Ctimes%20z%5E4%7D)
is
![x^{10}z^7](https://tex.z-dn.net/?f=x%5E%7B10%7Dz%5E7)
</h3>
Step-by-step explanation:
Given expression is x to the 12th power times z to the 11th power all over x to the 2nd power times z to the 4th power.
The given expression can be written as ![\frac{x^{12}\times z^{11}}{x^2\times z^4}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E%7B12%7D%5Ctimes%20z%5E%7B11%7D%7D%7Bx%5E2%5Ctimes%20z%5E4%7D)
<h3>To choose the correct simplification of the given expression :</h3>
Now we have to simplify the given expression as below
![\frac{x^{12}\times z^{11}}{x^2\times z^4}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E%7B12%7D%5Ctimes%20z%5E%7B11%7D%7D%7Bx%5E2%5Ctimes%20z%5E4%7D)
( by using the identity
)
![=(x^{12}.x^{-2})\times (z^{11}.z^{-4})](https://tex.z-dn.net/?f=%3D%28x%5E%7B12%7D.x%5E%7B-2%7D%29%5Ctimes%20%28z%5E%7B11%7D.z%5E%7B-4%7D%29)
( by using the identity
)
![=x^{10}\times z^7](https://tex.z-dn.net/?f=%3Dx%5E%7B10%7D%5Ctimes%20z%5E7)
![=x^{10}z^7](https://tex.z-dn.net/?f=%3Dx%5E%7B10%7Dz%5E7)
∴ ![\frac{x^{12}\times z^{11}}{x^2\times z^4}=x^{10}z^7](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E%7B12%7D%5Ctimes%20z%5E%7B11%7D%7D%7Bx%5E2%5Ctimes%20z%5E4%7D%3Dx%5E%7B10%7Dz%5E7)
<h3>The correct simplification for the given expression
![\frac{x^{12}\times z^{11}}{x^2\times z^4}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E%7B12%7D%5Ctimes%20z%5E%7B11%7D%7D%7Bx%5E2%5Ctimes%20z%5E4%7D)
is
![x^{10}z^7](https://tex.z-dn.net/?f=x%5E%7B10%7Dz%5E7)
</h3><h3>Hence option A)
![x^{10}z^7](https://tex.z-dn.net/?f=x%5E%7B10%7Dz%5E7)
is correct answer.</h3>
The answer is B. Each lb of cranberries is 2.52
Hope this helps!
Answer:
Line 1 is 1/3
Line 2 is 1/3 as well
Choice 1
Step-by-step explanation:
<u>Rise over run</u>
<em><u>Line 1:</u></em>
![\frac{(7)-(3)}{(6)-(-6)}](https://tex.z-dn.net/?f=%5Cfrac%7B%287%29-%283%29%7D%7B%286%29-%28-6%29%7D)
![\frac{4}{12}](https://tex.z-dn.net/?f=%5Cfrac%7B4%7D%7B12%7D)
<u>Simplify:</u>
1/3
<em><u>Line 2:</u></em>
![\frac{(2)-(1)}{(-3)-(-6)}](https://tex.z-dn.net/?f=%5Cfrac%7B%282%29-%281%29%7D%7B%28-3%29-%28-6%29%7D)
![\frac{1}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B3%7D)
1/3
1 is Paralell to 2 because they have the same slope
I hope this helps! :D
Pls give thx and brainliest if i’m right!
Answer:
4th option
Step-by-step explanation:
x² - 2x - 3 = 0 ( add 3 to both sides )
x² - 2x = 3
using the method of completing the square
add ( half the coefficient of the x- term )² to both sides
x² + 2(- 1)x + 1 = 3 + 1
(x - 1)² = 4
Answer:
what is the equation?
Step-by-step explanation: